COIN-operated anthropology: cultural knowledge, American counterinsurgency and the rise of the Afghan diaspora - Zafar, M (2016)
This thesis explores the encounter between the Afghan-American community and the U.S. military-industrial complex in the production of cultural knowledge for counterinsurgency (COIN) operations in Afghanistan. It focuses on the narratives mobilized as 'expertise' by Afghan-American contractors from the major diaspora hubs in California and Virginia, who were employed as role-players, translators, and cultural advisors by the U.S. military and defense contractors. I discuss how such narratives gained currency and shaped the perceptions of Afghanistan in the U.S. foreign and security policy communities. The goal of the thesis is to demonstrate the extent to which COIN-centered cultural knowledge production both defined political strategies toward Afghanistan and also reconstituted the Afghan diaspora in America. The thesis contributes to emergent ethnographic studies on militarism by looking at its effect on American society in general and the Afghan diaspora in particular. The broader application of the thesis findings is to move beyond critiques of the troubled connection between anthropology and the military, and to analyze the relationship between citizens and the state in terms of national and biopolitical security.